Efficacy and immunogenicity of a single dose of human papillomavirus vaccine compared to no vaccination or standard three and two-dose vaccination regimens: A systematic review of evidence from clinical trials. Issue 6 (5th February 2020) - Whitworth, Hilary S.; Gallagher, Katherine E.; Howard, Natasha; Mounier-Jack, Sandra; Mbwanji, Gladys; Kreimer, Aimée R.; Basu, Partha; Kelly, Helen; Drolet, Mélanie; Brisson, Marc; Watson-Jones, Deborah
Highlights: We reviewed the efficacy and immunogenicity of 1 vs. 0, 2 or 3 HPV vaccine doses in clinical trials. HPV16/18 infection was rare in all HPV vaccine recipients, regardless of number of doses received (3, 2 or 1). Frequency of infection was significantly lower in 1-dose recipients than in unvaccinated controls. Most vaccine recipients produced HPV16/18 antibodies, but titres were lower with 1 dose compared to 2 or 3 doses. 1-dose results are promising, and ongoing purpose-designed, prospectively randomised trials will provide further evidence. Abstract: Objectives: This study aimed to systematically review the literature on the efficacy and immunogenicity of single-dose HPV vaccination compared to no vaccination or multi-dose schedules among vaccine trial participants. Methods: Medline, EMBASE, Global Health Database and Cochrane Central Register of Controlled Trials were searched for publications and conference abstracts (dated January 1999-August 2018) using MeSH and non-MeSH terms for human papillomavirus AND vaccines AND (immunogenicity OR efficacy/effectiveness) AND dosage. Search results were screened against pre-specified eligibility criteria. Data were extracted from included articles, and a narrative synthesis conducted on efficacy against HPV16/18 infection and humoral immunogenicity. Results: Seven of 6, 523 unique records identified were included in the review. Six were nested observational studies of participants randomised to receive two or three doses in three large HPV vaccine trials, in which some participants did not complete their allocated schedules. One small pilot study prospectively allocated participants to receive one or no vaccine dose. Frequency of HPV16/18 infection was low (e.g. <1% for 12-month-persistent infection) in all vaccinated participants up to seven years post vaccination and did not significantly differ by number of doses (p > 0.05 in all cases). Frequency of infection was significantly lower in one-dose recipients compared to unvaccinated controls (p < 0.01 for all infection endpoints in each study). HPV16/18 seropositivity rates were high in all HPV vaccine recipients (100% in three of four studies reporting this endpoint), though antibody levels were lower with one compared to two or three doses. Conclusions: This review supports the premise that one HPV vaccine dose may be as effective in preventing HPV infection as multi-dose schedules in healthy young women. However, it also highlights the paucity of available evidence from purpose-designed, prospectively-randomised trials. Results from ongoing clinical trials assessing the efficacy and immunogenicity of single-dose HPV vaccination compared to currently-recommended schedules are awaited.